2005
DOI: 10.1074/jbc.m500733200
|View full text |Cite
|
Sign up to set email alerts
|

Glucosepane Is a Major Protein Cross-link of the Senescent Human Extracellular Matrix

Abstract: The extracellular matrix in most tissues is characterized by progressive age-related stiffening and loss of proteolytic digestibility that are accelerated in diabetes and can be duplicated by the nonenzymatic reaction of reducing sugars and extracellular matrix proteins. However, most cross-links of the Maillard reaction described so far are present in quantities too low to account for these changes. Here we have determined in human skin and glomerular basement membrane (GBM) collagen the levels of the recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
143
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(149 citation statements)
references
References 52 publications
3
143
0
Order By: Relevance
“…In this aspect, our in vitro nonoxidative incubation results conform well with the predominant level of glucosepane observed during analysis of in vivo human tissue modifications. 11,12 Most established protocols and routine methods used to identify and confirm cross-links in vivo utilize complete acid hydrolysis or exhaustive enzymatic digestion of proteins to the constituent amino acids, and amino acids with modifications. 11,22 The cross-links identified by these protocols will include both intra-and intermolecular cross-links.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this aspect, our in vitro nonoxidative incubation results conform well with the predominant level of glucosepane observed during analysis of in vivo human tissue modifications. 11,12 Most established protocols and routine methods used to identify and confirm cross-links in vivo utilize complete acid hydrolysis or exhaustive enzymatic digestion of proteins to the constituent amino acids, and amino acids with modifications. 11,22 The cross-links identified by these protocols will include both intra-and intermolecular cross-links.…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory provided additional data supporting the premise that glucosepane is the single major glycation derived cross-link known to date in aging human skin and glomerular basement collagen. 12 In addition, its levels are dramatically elevated in diabetes, 13 a condition that is associated with increased stiffness of all collagenrich tissues. Glucosepane levels increased up to ~2 nmol/mg collagen in old nondiabetic controls, and further increased to ~4.3 nmol/mg in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…1A) [13]. Recently, it has been found that among all different AGEs in human tissues the most abundant is glucosepane, a lysine-arginine crosslinking product [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Fructoselysine is a major protein adduct in extracellular matrix proteins, haemoglobin, lens proteins and other cells in which glucose permeates freely. It is the precursor to glucosepane, a lysine-arginine protein cross-link that is increased severalfold in diabetes [1], as well as several glycoxidation products [2]. For this reason, considerable efforts are being deployed to find ways to block or reverse its formation.…”
mentioning
confidence: 99%